In Vitro Susceptibility Testing of Clinical Isolates of Chlamydia trachomatis. Issue 1 (1993) - Martens, Mark G.; Faro, Sebastian; Maccato, Maurizio; Riddle, Gerald; Hammill, Hunter; Wang, Y.
Abstract : Penicillin class antibiotics have demonstrated varying degrees of in vivo and in vitro success when tested against Chlamydia trachomatis . The activity of ampicillin-sulbactam, an agent commonly utilized in the treatment of pelvic infections, was tested to ascertain if any antichlamydial activity is present. Up to six endocervical isolates of C. trachomatis were tested against each of five antibiotics including doxycycline, erythromycin, clindamycin, ampicillin/sulbactam, and sulbactam alone. McCoy cell monolayers were inoculated with high inclusion counts of 10, 000–30, 000 inclusion-forming units (IFU) per coverslip, and exposed to each antibiotic. Up to nine subsequent antibiotic free culture passes were performed to assess the viability of abnormal inclusions. Doxycycline, erythromycin, and clindamycin achieved 100% eradication of inclusions at concentrations of 4.0, 2.0, and 1.0 µg/mL. Exposure to ampicillin/sulbactam resulted in a greater than 99% reduction in the inclusion count at 32.0 µg/mL, while sulbactam by itself demonstrated considerably less activity. Abnormal inclusions were noted only in the ampicillin/sulbactam exposed cells, and these, plus all inclusions remaining following sublethal exposure to the other antibiotics, resulted in regrowth to control levels in subsequent passes. Doxycycline and erythromycin demonstrated excellent activity. Clindamycin and ampicillin/sulbactam also significantly reduced inclusion formation, and therefore may provide adequate C. trachomatis coverage in patients receiving these antibiotics for pelvic infections.